Screening of Tropical Plants for the Presence of Bioactive Compounds - Rahmani, Mawardi; Mohd Ismail, Hazar; Ahmad, Fariedah; Manas, Abd Rahman; Sukari, Mohd Aspollah (1992)
The use of synthetic pesticides and herbicides to control insect and weed pests has posed substantial problems due to their persistence in the environment, insect resistance and high mammalian toxicity. On the other hand. plant-de1ived insecticide are more readily biodegraded, less likely to contaminate the environment and less toxic to non target organism.s. Hence, the search for new sources of such compounds from plants has gained popularity amongst researchers. A screening procedure far the presence of bioactive compounds from plant sources by using brim: shrimp as the general bio assay has been can;ed out and a number of plant species has been identified for further detailed studies. The crude extracts and purified samples were further tested using other more specific bioassay methods.